2015
DOI: 10.1002/pds.3757
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of liver injury among cancer patients receiving chemotherapy in an integrated health system

Abstract: Abnormal LLTs are common in chemotherapy-treated patients. Medical record review showed that the incidence of Hy's law events is rare. These data provide context for evaluating DILI in clinical trials and postmarketing surveillance of anticancer therapies, understanding that automated data alone may substantially overestimate the number of Hy's law cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Studies from Asia or Australia were published in more recent years. Majority of the studies included adult populations (62%), two studies (7%) included children aged 18 years and below, eight studies (28%) included a mixed adult and children population, while age limit was not reported in one study . Apart from two prospective studies with shorter study periods, the rest of the studies were conducted retrospectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies from Asia or Australia were published in more recent years. Majority of the studies included adult populations (62%), two studies (7%) included children aged 18 years and below, eight studies (28%) included a mixed adult and children population, while age limit was not reported in one study . Apart from two prospective studies with shorter study periods, the rest of the studies were conducted retrospectively.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to reporting quality, selection criteria and detection algorithm were generally well‐reported, with the exception of two studies which did not list out the specific diagnosis codes. Eleven studies did not report the expertise of adjudicators in confirming the DILI cases. Only seven studies performed well in generalizability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, it is not the only causality tool employed by the DILIN, which has created its own additional criteria based on expert opinion incorporated into RUCAM, as illustrated in Table 5[59,118]. Even with more accurate causality tools, the clinical problems in diagnosing DILI in the setting of underlying CLD[69,72], malignancy[119], or congestive heart failure[120] still rests heavily on physician’s expertise which cannot easily be substituted by scoring systems[60,69]; a fact which is even more relevant in the face of HILI, because of the unknown and unregulated ingredients often incorporated into HDS[73], again indicating the need for future research in this field[121]. …”
Section: Diagnosing and Establishing Causalitymentioning
confidence: 99%
“…In previous years, combined chemotherapy has been proved to be an import way in increasing the efficacy of the treatment of hepatocarcinoma ( 4 ) and cisplatin treatment combined with specific molecular targeted drug has attracted increased attention. As an oral antidiabetic drug, metformin is the first-line drug for the treatment of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%